SEEDING TECHNIQUE Cyprinus carpio IN FRESHWATER AQUACULTURE UNIT OF BUSINESS (UPBAT) PASURUAN, EAST JAVA - Dimas Galang Prakosa; Rizqi Ayu Ratnayu (Faculty of Science and Technology University Ibrahimy, 2016)
This research was conducted at Unit of business Freshwater Aquaculture (UPBAT) Pasuruan, East Java, on July – September 2015. The purpose of this study was to determine the fish hatchery techniques of Cyprinus carpio in UPBAT Pasuruan. Hatchery goldfish in UPBAT include aircraft maintenance, preparation for spawning tub, parent selection, breeding, seed maintenance and feeding. Results obtained are spawning carp be done naturally by mass system, using the parent goldfish namely 4 female parent and 8 male parent of a total holding in UPBAT. In one spawning produced ± 240,000 eggs, resulting in a year with three times the number of eggs obtained spawning ± 720,000 eggs. The fertilized eggs will hatch 2-3 days after spawning, spawning once the larvae thus obtained ± 236 128 ± 708 384 larvae in a year so the HR = 98.38%. Once spawning is obtained approximately 205 984 fish seed so that in one year earned approximately 617 952 fish seed which means SR = 87.23%. Feeding the form of natural silk worms do after the yolk will run out (± 3-4 days) at a dose of feeding as many as 3% of the body weight of larvae / day approximately 100 grams, to 236 128 larvae. As for the mains feed pellets was given at a dose of feeding 3% of the parent body weight / day 2 kg for the mains and feed on the seeds with a dose feeding 3% of the seed weight / day to 800 grams to 205 984 fish seed.